Recapitalizing Banking Systems : Implications for Incentives and Fiscal and Monetary Policy - Honohan, Patrick (World Bank, Washington, DC, 2013)
In the aftermath of a banking crisis, most attention is rightly focused on allocating losses, rebuilding properly managed institutions, and achieving debt recovery. But the authorities' decision to use budgetary funds to help restructure a large failed bank or banking system also has consequences for the incentive structure for the new bank management, for the government's budget, and for monetary stability. These issues tend to be lumped together, but each should be dealt with in a distinctive manner. The author points out, among other things, how apparent conflicts between the goals in each of these areas can be resolved by suitably designing financial instruments and appropriately allocating responsibility between different arms of government. First the government must have a coherent medium-term fiscal strategy that determines broadly how the costs of the crisis will be absorbed. Then the failed bank must be securely reestablished with enough capital and franchise value to move forward as a normal bank. This will typically entail new financial institutions involving the government on both the asset and the liability sides of the bank's balance sheet. The bank should not be left with mismatches of maturity, currency, repricing. Assets that are injected should be bankable and preferably negotiable. The liability structure should give bank insiders the incentive to manage the bank prudently. Financial instruments can be complex and sophisticated but only if the government has the credibility to warrant market confidence that it will deliver on the contracts rather than trying to use its lawmaking powers to renege. Innovative use of segregating sinking funds and "Brady"-type bonds can help where government credibility is weak. Restructuring the bank will alter the size, maturity, and other characteristics of the government's debt. These characteristics should be optimized separately and with the market as a whole, not just the affected banks.